2006
DOI: 10.1007/s00421-006-0213-x
|View full text |Cite
|
Sign up to set email alerts
|

The validity of predicting maximal oxygen uptake from perceptually regulated graded exercise tests of different durations

Abstract: The purpose of this study was to assess the validity of predicting maximal oxygen uptake [V(.-)((O)(2)(max))] from sub-maximal V(.-)((O)(2)) values elicited during perceptually regulated exercise tests of 2- and 4-min duration. Nineteen physically active men and women (age range 19-23 years) volunteered to participate in two graded exercise tests to volitional exhaustion to measure V(.-)((O)(2)(max)) [V(.-)((O)(2)(max))(GXT)], at the beginning and end of a 2-week period, and four incremental, perceptually regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
72
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 29 publications
(59 reference statements)
11
72
0
5
Order By: Relevance
“…These findings are in agreement with previous research by Eston et al 7,9 The current study shows that the high RPE range (that is, RPE 9-17) may be excluded from the second perceptually guided test without loss of accuracy in predicting .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are in agreement with previous research by Eston et al 7,9 The current study shows that the high RPE range (that is, RPE 9-17) may be excluded from the second perceptually guided test without loss of accuracy in predicting .…”
Section: Discussionsupporting
confidence: 94%
“…VO 2 max in healthy, able-bodied individuals during leg cycling. [7][8][9] There were no significant differences between measured and predicted .…”
Section: Discussionmentioning
confidence: 77%
“…This RPE-guided effort model is in contrast to the paradigm where investigators preset workloads on a laboratory treadmill or cycle ergometer, as described earlier. Studies employing land-based exercise have confirmed the usefulness of employing such an RPE-guided approach to systematically self-modulate exercise intensity during a graded exercise protocol (Eston, Faulkner, Mason, & Parfitt, 2006;Eston, Lamb, Parfitt, & King, 2005;Eston, Lambrick, Sheppard, & Parfitt, 2008;Faulkner et al, 2007). Eston et al (2005Eston et al ( , 2006 and Faulkner et al (2007) found a strong, positive correlation between VO 2 and RPE.…”
mentioning
confidence: 85%
“…Studies employing land-based exercise have confirmed the usefulness of employing such an RPE-guided approach to systematically self-modulate exercise intensity during a graded exercise protocol (Eston, Faulkner, Mason, & Parfitt, 2006;Eston, Lamb, Parfitt, & King, 2005;Eston, Lambrick, Sheppard, & Parfitt, 2008;Faulkner et al, 2007). Eston et al (2005Eston et al ( , 2006 and Faulkner et al (2007) found a strong, positive correlation between VO 2 and RPE. In addition, the above studies predicted maximal aerobic power (VO 2 max) by extrapolating the relationship between submaximal VO 2 (y-axis) regressed on preset RPE (x-axis; RPE = 9, "very light"; 11, "light"; 13, "somewhat hard"; 15, "hard"; 17, "very hard") out to a theoretical maximum of RPE 20.…”
mentioning
confidence: 85%
See 1 more Smart Citation